(untitled) (Latakia University Journal -Medical Sciences Series, 2018)
Background: chemotherapy is the only treatment for metastatic triple negative breast cancer, and many studies strongly suggest the role and importance of platinum- based chemotherapy in improving treatment outcomes in this group of patients. The aim of this retrospective study was to evaluate the role of platinum-based chemotherapy in this group of patients in terms of objective response rate and median progression – free survival. Patients and methods: we conducted a retrospective study of 68 patients treated for metastatic triple negative breast cancer between February 2010 and January 2016, at the chemotherapy and radiotherapy center of Tishreen hospital. The patients received platinum based chemotherapy (Cisplatin or Carboplatine) in combination with other cytotoxic (Gemcitabine, Navelbine, Paclitaxel, Docetaxel and cyclophosphamid) Results: The objective response rate was 51,4% , complete response(CR) in 3 patients and partial response (PR) in 32 patients, 12 patients had a stable disease (SD),while 19 patients had progression diseases (PD). Median progression free survival (PFS)was 7,67 months (2-18), in patients without visceral metastases was 11,47 months (9-18) vs 5,95 months (2-8) in the case of visceral metastases The best combination was between cisplatin and gemcitabine with PFS 10,06 months (6-15),while PFS in combination between carboplatin and docetaxel was 9,08 months (5-18). Toxicity was acceptable, the most common side effect is myelosuppression especially in carboplatin treated group, nausea and vomiting in cisplatin treated group. Conclusions: platinum-based chemotherapy is an important therapeutic choice in metastatic triple negative breast cancer, it has significant activity and a favorable safety. أهمية ودور أملاح البلاتين في المعالجة الكيميائية لسرطان الثدي النقائلي الثلاثي السلبي تعتبر المعالجة الكيميائية هي العلاج الوحيد في حالة سرطان الثدي النقائلي ثلاثي السلبية, وتشير العديد من الدراسات بقوة إلى دور وأهمية أملاح البلاتين في تحسين نتائج المعالجة عند هذه المجموعة من المريضات. تهدف هذه الدراسة الراجعة إلى تقييم دور المعالجة بأملاح البلاتين عند هذه المجموعة من المريضات من حيث معدل الاستجابة وزمن البقيا بدون نكس. شملت الدراسة 68 مريضة من المراجعات لمركز المعالجة الكيميائية والشعاعية في مشفى تشرين الجامعي بين شباط 2010 وكانون الثاني 2016 ولديهن سرطان ثدي نقائلي ثلاثي السلبية (ER-,PR-,HER2- ) والمعالجات بأملاح البلاتين (سيسبلاتين, كاربوبلاتين) بالمشاركة مع مركبات دوائية أخرى (جيمسيتابين, دوسيتاكسيل, نافيلبين, باكليتاكسيل وسيكلوفوسفاميد). بلغ معدل الاستجابة 51,4% (استجابة تامة عند ثلاث مريضات واستجابة جزئية عند 32 مريضة),بينما استقر حجم الإصابة لدى 12 مريضة وحدث تفاقم للمرض عند 19 مريضة. كان زمن البقيا بدون نكس 7,67 شهر (2-18 ) وكان أفضل عند المريضات بدون نقائل حشوية 11,47 شهر (9-18 ) مقابل 5,95 شهر (2-8 ) في حالة النقائل الحشوية. كانت أفضل المشاركات الدوائية بين السيسبلاتين والجمسيتابين مع زمن البقيا بدون نكس10,06 أشهر (6-15 ) يليه المشاركة بين الكاربوبلاتين والدوسيتاكسيل 9,08 أشهر (5-18 ). بالمقابل كان التحمل العلاجي مقبول وأكثر التأثيرات الجانبية حدوثا هو التثبيط النقوي وخاصة في المشاركات الدوائية مع الكاربوبلاتين بالإضافة للغثيان والإقياءات وارتفاع أرقام الكرياتينين عند المريضات المعالجات بالسيسبلاتين. تعتبر المعالجة بأملاح البلاتين من الخيارات العلاجية الهامة من الناحية السريرية عند النساء المصابات بسرطان ثدي نقائلي ثلاثي السلبية من حيث معدل الاستجابة وزمن البقيا بدون نكس مع سمية دوائية مقبولة.